Two-dimensional antiferromagnetic topological insulators in KCuSe/NaMnBi van der Waals heterobilayers. Issue 40 (11th October 2022) - Ma, Hongkai; Li, Bingyang; Zou, Xiaorong; Hu, Xiangting; Dai, Ying; Huang, Baibiao; Niu, Chengwang
Abstract : The interplay between band topology and magnetism plays a central role in achieving exotic physical phenomena and innovative spintronics applications. Abstract : The interplay between band topology and magnetism plays a central role in achieving exotic physical phenomena and innovative spintronics applications. While prior works have mainly focused on ferromagnetic matter, little is known about the manipulation of band topology in antiferromagnets. Here, we report the emergence of a two-dimensional (2D) antiferromagnetic topological insulator (AFM TIs) by proximity coupling a 2D TI and a normal AFM insulator, and remarkably realize it in a concrete example of the KCuSe/NaMnBi heterobilayer. The first-principles calculations show that a band gap as large as 63.8 meV can be opened up by spin–orbit coupling, revealing the possible application even at room temperature. The size of the band gap depends on the separation between KCuSe and NaMnBi QLs, which can be switched experimentally by applying external strain. Moreover, the heterobilayer presents an integer topological invariant with a value of Z 2 = 1 and a pair of gapless edge states. The findings not only broaden the range of 2D AFM topological quantum materials, but could also inspire more research in van der Waals heterobilayers for topological spintronics.